Biological Effect of Controlling Rhizoctonia Solani, The Fungus that Causes Cucumber Root Rot Disease - Radhi, Kifah Hadi (Journal of Science in Medicine and Life, 2025)
This study aimed to identify the fungal pathogen responsible for cucumber root rot disease in Babylon province and to study the biological management of this disease. The roots of diseased cucumber plants were used to isolate the fungus Rhizoctonia solani. where the pathogenicity tests were conducted for twelve isolates on the Cabbage seeds. Each isolate showed its high pathogenicity in inhibiting the germination of Cabbage seeds. Then, pathogenicity tests were conducted for the strongest four pathogenic isolates in infecting cucumber plants, namely R.s11, R.s10, R.s7, and R.s5. Moreover, the antagonistic potential of Bacillus subtilius was likewise tested, and the fungus Trichoderma harzianum and Penicillium gresiofulvum with the pathogenic fungus R.solani, The study findings showed that inhibition percentage was 100%, 92%, and 90%, respectively. Finally, the lath house The results demonstrated how well biological control methods inhibited the harmful fungus R.solani.